Compliance within a Regulatory Framework in Implementing Public Road Construction Projects (Construction Economics and Building, 2018)
The construction industry faces a lack of compliance with policy that in Uganda public road construction projects affects the attainment of Government goals and disrupts infrastructure project delivery. For decades, public entities have been known for a lack of compliance that manifest in: poor performance, poor personnel management, poor resource utilization and unprofessionalism. In Uganda, this has resulted in several restructures aimed at improving service delivery. Despite this, compliance remains an issue. The purpose of this study is to establish factors affecting compliance within a public procurement regulatory framework in public road construction projects and foster economic development. A cross-sectional research design including a structured self-administered questionnaire survey and PLS-SEM data analysis by SmartPLS3 was conducted. The research reveals that three factors positively affect compliance with a regulatory framework that govern public road construction projects; sanctions on staff, inefficiency of the public procurement regulatory framework and contractors’ resistance to non-compliance. While a further three factors have little positive effect on compliance; familiarity, monitoring activities and professionalism. Hence, the research contributes to construction management by showing that sanctions, perceived inefficiency and contractors’ resistance significantly enhance compliance within a public procurement regulatory framework.